2000
DOI: 10.1067/mcp.2000.110215
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro induction of human cytochrome P4503A4 by dexamethasone

Abstract: These data demonstrate that dexamethasone at doses used clinically increased CYP3A4 activity with extensive intersubject variability and that the extent of CYP3A4 induction was, in part, predicted by the baseline activity of CYP3A4 in both healthy volunteers and human hepatocyte cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 25 publications
7
117
0
Order By: Relevance
“…We hypothesize that the centre effect is related to steroid use and that continuous therapy leads to an induction of CYP enzymes and higher tacrolimus CL/F. Various studies have demonstrated an induction of CYP3A enzymes by corticosteroid therapy [42][43][44]. Although controversial, studies have identified corticosteroid therapy as a significant factor towards tacrolimus CL/F [9,27,[45][46][47].…”
Section: Figurementioning
confidence: 99%
“…We hypothesize that the centre effect is related to steroid use and that continuous therapy leads to an induction of CYP enzymes and higher tacrolimus CL/F. Various studies have demonstrated an induction of CYP3A enzymes by corticosteroid therapy [42][43][44]. Although controversial, studies have identified corticosteroid therapy as a significant factor towards tacrolimus CL/F [9,27,[45][46][47].…”
Section: Figurementioning
confidence: 99%
“…The total antipyrine clearance and clearance for production of metabolites observed for the population studied (Table 2) were considerably higher than those reported for different populations including patients treated with antiepileptics such as phenytoin and/or carbamazepine (22,27). It should be emphasized, however, that dexamethasone, an inducer of CYP3A4 (33,34), is able to potentially induce the formation of OHA and, consequently, to increase total antipyrine clearance. McCune et al (34) reported that dexamethasone at clinically used doses increased CYP3A4 activity with extensive intersubject variability in healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized, however, that dexamethasone, an inducer of CYP3A4 (33,34), is able to potentially induce the formation of OHA and, consequently, to increase total antipyrine clearance. McCune et al (34) reported that dexamethasone at clinically used doses increased CYP3A4 activity with extensive intersubject variability in healthy volunteers. ASON in man are available, the results presented here suggest the involvement of the same or similar enzymes in the oxidation of antipyrine and ASOX.…”
Section: Resultsmentioning
confidence: 99%
“…The chemosensitivity of the primary tumor is the major determinant of the response to systemic treatment for brain metastases (92,95), although asymptomatic brain metastases may have lower responses than systemic tumors to systemic chemotherapy (82). Dexamethasone and enzyme-inducing anti-epileptic drugs (EIAEDs) can induce cytochrome p450 3A isoenzymes, including CYP3A4, which metabolizes chemotherapeutic agents (96,97) including paclitaxel, irinotecan, vinorelbine, cyclophosphamide, doxorubicin, etoposide, ifosfamide, teniposide, erlotinib, and gefitinib. Therefore, co-administration of EIAEDs or dexamethasone may increase the metabolism of chemotherapeutic agents, lower plasma concentrations, and reduce efficacy.…”
Section: Discussionmentioning
confidence: 99%